Effectiveness of the Expanded Public Works Programme (EPWP) in empowering the youth through job creation. - Banda, Elsie Hleziphi (My University, 2016)
This study applies the ‘theory of change’ to assess the outcome of the National Youth Service (NYS) Learnership intervention in Mpumalanga Province. The Department of Public Works Roads and Transport in Mpumalanga implemented the programme on behalf of the Government whose main objective was to make its participants employ-able. The programme assessment applied a qualitative strategy and a cross-sectional de-sign. Respondents of the study were participants who participated in the programme during 2010, as well as the programme manager. The study found that though participants were generally satisfied about the pro-gramme they also felt that it did not meet their expectations and neither did it meet the outcomes entrenched in the NYS. Practical expertise gained through the programme is fundamental, but insufficient to address the participants’ employability. The graduates were not market ready, nor were there sustainable exit pathways through which partici-pants could ultimately benefit from the skills they obtained during training. In addition, the programme training level is below a formal qualification, thus participants of the programme are not fully trained artisans. Therefore, the main objective of programme was somewhat achieved with some learners temporarily employed and applying the skill they received.
MM
Keywords: Public works -- South Africa. Economic development -- South Africa. Job creation -- South Africa. Youth -- Employment -- South Africa.